The taming of the skew: asymmetric inflation risk and monetary policy - Andrea De Polis; Leonardo Melosi; Ivan Petrella (European Central Bank (ECB), 2025)
We document that inflation risk in the U.S. varies significantly over time and is often asymmetric. To analyze the macroeconomic effects of these asymmetric risks within a tractable framework, we construct the beliefs representation of a general equilibrium model with skewed distribution of markup shocks. Optimal policy requires shifting agents' expectations counter to the direction of inflation risks. We perform counterfactual analyses using a quantitative general equilibrium model to evaluate the implications of incorporating real-time estimates of the balance of inflation risks into monetary policy communications and decisions.
Keywords: E52; E31; C53; 330; Asymmetric risks; optimal monetary policy; balance of inflation risks; risk-adjusted inflation targeting; flexible average inflation targeting